Family-based treatment for children and adolescents with eating disorders: a mixed-methods evaluation of a blended evidence-based implementation approach. Issue 1 (20th November 2019) - Couturier, Jennifer; Kimber, Melissa; Barwick, Melanie; Woodford, Tracy; Mcvey, Gail; Findlay, Sheri; Webb, Cheryl; Niccols, Alison; Lock, James
Abstract: In this study, we evaluated a blended implementation approach with teams learning to provide family-based treatment (FBT) to adolescents with eating disorders. Four sites participated in a sequential mixed method pre–post study to evaluate the implementation of FBT in their clinical settings. The implementation approach included: (a) preparatory site visits; (b) the establishment of implementation teams; (c) a training workshop; (d) monthly clinical consultation; (e) monthly implementation consultation; and (f) fidelity assessment. Quantitative measures examining attitudes toward evidence-based practice, organizational learning environment and organizational readiness for change, as well as, individual readiness for change were delivered pre- and postimplementation. Correlational analyses were used to examine associations between baseline variables and therapist fidelity to FBT. Fundamental qualitative description guided the sampling and data collection for the qualitative interviews performed at the conclusion of the study. Seventeen individuals participated in this study (nine therapists, four medical practitioners, and four administrators). The predetermined threshold of implementation success of 80% fidelity in every FBT session was achieved by only one therapist. However, mean fidelity scores were similar to those reported in other studies. Participant attitudes, readiness, and self-efficacy were not associated with fidelity and did not change significantly from pre- to postimplementation. In qualitative interviews, all participants reported that the implementation intervention was helpful in adopting FBT. Our blended implementation approach was well received by participants. A larger trial is needed to determine which implementation factors predict FBT fidelity and impact patient outcomes.